2021
DOI: 10.3390/ijms22115482
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking Analysis and Biological Evaluations of Saccharide-Modified Thiadiazole Sulfonamide Derivatives

Abstract: A series of saccharide-modified thiadiazole sulfonamide derivatives has been designed and synthesized by the “tail approach” and evaluated for inhibitory activity against carbonic anhydrases II, IX, and XII. Most of the compounds showed high topological polar surface area (TPSA) values and excellent enzyme inhibitory activity. The impacts of some compounds on the viability of HT-29, MDA-MB-231, and MG-63 human cancer cell lines were examined under both normoxic and hypoxic conditions, and they showed certain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In the study of Nemr and coworkers, the benzenesulfonamide derivatives showed a significant experimental activity towards hCA-IX, and they were bound to the same group of amino acids (HIS94, THR200, and GLU106). The modified thiadiazole sulfonamide derivatives formed hydrogen bonds with GLN92 and THR200, and hydrophobic interactions with HIS94, VAL121, and LEU199 [19]. These results compare quite well with the presented ones from this study.…”
Section: Active Site Confirmation and Molecular Docking Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…In the study of Nemr and coworkers, the benzenesulfonamide derivatives showed a significant experimental activity towards hCA-IX, and they were bound to the same group of amino acids (HIS94, THR200, and GLU106). The modified thiadiazole sulfonamide derivatives formed hydrogen bonds with GLN92 and THR200, and hydrophobic interactions with HIS94, VAL121, and LEU199 [19]. These results compare quite well with the presented ones from this study.…”
Section: Active Site Confirmation and Molecular Docking Analysissupporting
confidence: 89%
“…The protein-ligand interactions between coumarin-neurotransmitter derivatives and amino acids in the active site of the hCA-IX receptor were examined using molecular docking. This protein was taken as a docking model for the explanation of the antitumor experimental activity in several studies [17,19]. Additionally, this protein was chosen because the selected inhibitors (out of seven million compounds) of hCA-IX in the study by Salmas and co-workers showed structural similarities with the obtained compounds [20].…”
Section: Active Site Confirmation and Molecular Docking Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature was set to 300 K and the pressure was set to 1.01325 bar. Finally, the 100 ns MD simulations were carried out (record the time interval of each trajectory at every 100 PS) [ 60 , 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among those, 1,3,4-thiadiazoles gained substantial interest due to their widespread biological activity, including antimicrobial, anti-inflammatory, antithrombotic, antihypertensive, antituberculosis, anesthetic, anticonvulsant and antiulcer activities [ 11 , 12 , 13 , 14 , 15 , 16 ]. Furthermore, different researchers also particularly report 1, 3, 4-thiadiazole derivatives for their excellent anticancer activity, which are confirmed by desirable IG 50 and IC 50 values in inhibitory effect, such as Filanesib and compounds I–III ( Figure 1 ) [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%